ANALISIS SEBARAN OKSIGEN TERLARUT TERHADAP TOTAL SUSPENDED SOLID (TSS) DI PERAIRAN KETINGAN KABUPATEN SIDOARJO - Mochammad Rizqi Ramanda; Siti Zainab (LPPM Universitas Abdurrab, 2025)
Ketingan Waters is on the northeastern coast of Sidoarjo Regency, which directly borders Bangil Regency. Along the coast of Ketingan, there are rivers that empty into Ketingan. The high number of educators, not accompanied by the addition or provision of land for settlements, triggers residents to carry out activities, including industrial activities, and dispose of waste directly into river flows downstream, thereby reducing water quality. For this reason, efforts are needed to monitor the distribution of dissolved oxygen (DO) and total suspended solids (TSS) in the Ketingan area using Landsat 8 satellite imagery in 2019 - 2023. The aim of this research is to analyze the concentration of total suspended solids and the concentration of dissolved oxygen in the Ketingan Beach area of Sidoarjo Regency. It is hoped that this research can provide information about Ketingan waters for a database of uses in the field of civil engineering in planning and maintaining coastal buildings. The results of this analysis will be confirmed by sea surface conditions. The analysis results show that the in situ data values for TSS are 52 - 152 mg/L and DO are 5.47 - 7.89 mg/L. Image data with the highest correlation for TSS shows values of 49 - 250.99 mg/L and DO of 0.67 - 18.48 mg/L. In situ data and DO image data have a fairly strong correlation, namely 0.631766933, and TSS has a moderate negative correlation, namely -0.481086311